Family functioning, resilience, and depression among North Korean refugees. (30th November 2016) - Nam, Boyoung; Kim, Jae Yop; DeVylder, Jordan E.; Song, Ahyoung
Abstract: North Korean refugees in South Korea are at high risk of depression, but there are few studies exploring protective factors in this population. We hypothesized that family functioning (family adaptability and cohesion) and resilience would protect North Korean refugees from developing depressive symptoms. A subsample of 304 adult North Korean refugees drawn from the cross-sectional 2010 Nationwide Survey of Domestic Violence in South Korea was analyzed. Approximately 44% of respondents were identified as having depression, using scores on the Center for Epidemiological Studies Depression scale. In models capturing the full spectrum of depressive symptoms (continuous), family cohesion was significantly associated with depression, and the relationship was partially mediated by resilience. In models predicting clinical depression (dichotomous), resilience fully mediated the relationship between family cohesion and clinical depression. In contrast, family adaptability was not associated with depression or resilience in this sample. These findings suggest that assessing and enhancing family cohesion and resilience may be essential for professionals working with refugees, and that refugees without family support may be at particularly high risk for depression. Highlights: Family cohesion was significantly associated with less depression among North Korean refugees in South Korea. Resilience significantly mediated the relationship between family cohesion and depression. Refugees without family support may be at particularly high risk for depression. Family support and resilience may be modifiable protective factors among refugees.